歯科パノラマX線撮影における線量評価法 - 星野, 佳彦; 須藤, 高行; 福田, 淳也; 福島, 康宏; 天沼, 誠; 大竹, 英則 (日本放射線技術学会雑誌, 2009)
Purpose: There is no established method to determine a diagnostic reference level of panoramic radiology. As the basic principle of the panoramic radiology dose index (PRDI) and CT dose index (CTDI) is almost identical, we evaluated the usefulness of PRDI for this purpose.Methods: Using the imaging plate (IP) sandwiched between the 160-mm thick acrylic disks, horizontal radiation dose distribution was analyzed by the conventional radiographic technique. Panoramic exposure dose was measured using the CT ionizing chamber that was placed at the tracking focus. Beam height was used as measurement unit, and PRDI was normalized and calculated.Results: There were two foci showing the maximum exposure dose for this panoramic equipment, located symmetrically 45 mm away from the center of the object. The PRDI of medium-sized individuals measured by this method was 0.74 mGy.Conclusion: We suggested a method to evaluate a diagnostic reference level, measuring the dose of exposure focus, i.e., maximum dose on panoramic radiology.